SURFACING AND DOCUMENTING THE TRADITIONAL GA’DANG DISHES OF BAYOMBONG, NUEVA VIZCAYA AND ITS POTENTIAL AS A CULTURAL TOURISM ELEMENT - Niña Mae Bianca (Lembaga Penelitian Universitas Pasundan, 2017)
This study was undertaken to preserve and promote the traditional Ga’dang dishes of Bayombong, Nueva Vizcaya. Interviews were conducted among 20 Ga’dang respondents such as elders, barangay chairman and a researcher last February 2014 to obtain the information needed. Books, municipal records, Internet sources and barangay files were also compiled. From the general findings of the study, the following conclusions were drawn: (1) Their traditional dishes can be classified according to everyday and festive food. Everyday food are the dishes typically prepared such as ininaw, pinaracao, nilabbab, ginataang suso barale, while their festive foods usually prepared during special occasions and gatherings are inandela, laoya, tinuno and pinatarak; (2) The sources of food are rivers and streams where they obtain fish and shellfish. They also till their agricultural lands to grow crops and vegetables. Aside from these, they also practice livestock raising; (3) In terms of food preparation methods and procedures, they practice boiling, grilling, steaming and preserving through drying and salting; (4) They still adhere to their customary food beliefs and practices such as praying before preparing food, sharing of food with neighbors which is their gesture of showing generosity and offering of foods for the departed which is known as atang; (5) The traditional dishes have potentials as cultural tourism element because they are greatly associated with their customs, traditions and beliefs. Although some of their methods of preparation as well as recipes are not indigenous to them, they modified them such that they have developed them as distinctly Ga’dang dishes. In order to preserve and promote the traditional dishes, the younger Ga’dang generation should be taught about them so that they will be able to integrate them in their daily lives.